Onward maths 4 textbook (second edition) - Tan, Dr evelyn; Edgar, Katharine (Alston Publishing House Pte Ltd Singapore, 2014)
The ONWARD MATHS series is developed to cover the learning outcomes of the latest Cambridge Primary curriculum framework comprehensively. ONWARD MATHS builds a strong foundation of the subject through the use of well-researched and sound pedagogical principles. Adopting the popular Concrete- Pictorial-Abstract approach widely used in the Singapore mathematics curriculum, pupils are introduced to new concepts through concrete manipulatives and engaging pictorials before they are led to see their abstract symbolic representations. This allows pupils to have a deeper understating of key mathematical concepts, thus motivating them to learn. Content is also clearly structured and spiraled across the levels to ensure a gradual build-up and review of skills as pupils progress up the grades. At the same time, emphasis is given on developing pupils$1 (Bproblem-solving skills, critical thinking, as well as other 21st century skills.s